Alkaline serine protease from halatoerant Bacillus licheniformis BA17 - (:unkn) unknown (SPRINGER, 2009)
An alkaline protease from halotolerant Bacillus licheniformis BA17, isolated from Van Lake in Turkey, was purified 5.4 fold with 58% yield. The molecular weight was 19.7 kDa and the optimum temperature and pH were 60 degrees C and 10, respectively. The half-life of the pure enzyme was 38 h, 93 min, 14 min and 6 min at 40, 50, 60 and 70 degrees C, respectively. BA17 protease is very active at 30 degrees C between pH 8.0 and 10. Enzyme activity increased in the presence of Cu+2, Mg+2, Mn+2 and K+1 ions, Enzyme retained activity with 5% SDS (w/v) and 1% Triton X-100 (v/v). Inhibition with PMSF and EDTA suggested that the enzyme is a serine protease and is a metal-activated enzyme. Based on the N-terminal sequence of the first 13 amino acids, B. licheniformis BA17 alkaline protease did not show identity to any of those from other Bacillus species.
Keywords: alkaline protease; Bacillus licheniformis; enzyme purification and characterization; CLAUSII I-52; PURIFICATION; HALOTOLERANT; STRAIN; STABILITY; OXIDANT; ASSAY